Thermoelectric monitoring of thermal resistance in electronic systems - Abouellail, A.A.; Chang, J.; Soldatov, A.I.; Soldatov, A.A.; Kostina, M.A.; Vasiliev, I.M. (Karagandy University of the name of acad. E.A. Buketov, 2023)
The article proposes to apply the method of thermoelectric testing to determine the thermophysical parameters of the thermal interface. A thermal interface is located between metal surfaces, between which, thermoelectromotive force occurs during heating at any stage of the device operation. The obtained graphs of the temperature difference dependence on the heating time, measured by thermocouples, and measured using thermoelectromotive force confirm the accuracy of the thermoelectric method of testing. Graphs visualize the heat transfer process with thermal resistance variation, temperature fluctuations and the resulting thermoelectromotive force. The proposed method makes it possible to monitor thermal resistance with an error of less than 8 %.
Keywords: thermal interface; thermal resistance; thermoEMF; Seebeck effect; thermoelectric monitoring